The usage and perceived effectiveness of different recovery modalities in amateur and elite Rugby athletes - Tavares, F.; Healey, P.; Smith, T. B.; Driller, M. (Performance Enhancement & Health, 2017)
No differences were found for the perception of the importance of recovery between groups. Elite Rugby athletes use significantly more recovery modalities (~8 vs 3) in comparison to amateurs. Elite Rugby athletes implemented recovery modalities more often (~25 vs ~6 times per week) in comparison to amateurs. Elite Rugby athletes perceived 6 out of 11 recovery modalities to be more effective in comparison to amateurs.